Polarization Measurement Using Vortex Beams With Non-Integer Orbital Angular Momentum - Aning Ma; Zhongqiang Zhang; Yurong Wang; Di Geng; Xinyi Tian; Haofeng Huang (IEEE Photonics Journal, 2022)
Polarization measurement has been used for many optical applications in science and technology. Herein, we adopt a reliable method to measure the polarization parameters of incident light, including principal axis, chirality and ellipticity based on the superposition of two orthogonal vortex beams with non-integer topological charges (TCs). All three polarization parameters can be measured and analyzed by the interference pattern produced by the superposition of two vortex beams with ${\ell }_1 = 1$ and ${\ell }_2{\rm{ = 0}}{\rm{.5}}$ . The relationship between the principal axis of polarization and the interference pattern is deduced theoretically. The measurement results agree with the theoretical formulation very well. The advantages of simplicity make this method have a good application prospect in polarization measurement, optical communication, micro-particles manipulation and quantum science.